Hubungan antara Self Efficacy dengan Quarter Life Crisis pada Mahasiswa Psikologi Universitas Medan Area - Diantri Trisna Sari; Azhar Aziz (Universitas Medan Area, 2022)
The purpose of this research was to find correlation between Self Efficacy and Quarter Life Crisis of Psychology students at Medan Area University. This study uses the quantitative method, the subjects of this research are all 2017 classes of Psychology Students at Medan Area University. The number of sample in this research were 87 students. The sampling techniques in this study used a Purposive Sampling Technique. The data collection method was Likert Scale. Self Efficacy scale used in this research was made by Bandura (1997) and Quarter Life Crisis scale used in this research was made by Robbins and Wilner (2001). Data analysis technique used was Correlation Product Moment. The hypothesis propodes in this research were negative correlation between Self Efficacy and Quarter Life Crisis with assumption; the higher Self Efficacy was the lower Quarter Life Crisis became and vice versa. Based on the result of the analysis carried out, there indeed were negative correlation between Self Efficacy and Quarter Life Crisis. The result were proved by hypothetical mean of Self Efficacy on 55 and Quarter Life Crisis on 72.5 then empirical mean of Self Efficacy on 65.38 and Quarter Life Crisis on 59.72. Value or coefficient which the coefficient was -0.715 with p-value significance = 0.000 0.05 with a contribution weight of 51.2% .